Genomic Relatedness of Xanthomonas campestris Strains Causing Diseases of Citrus - Egel, D. S. (1991)
Xanthomonas campestris strains that cause disease in citrus were compared by restriction endonuclease analysis of DNA fragments separated by pulsed-field gel electrophoresis and by DNA reassociation. Strains of X. campestris pv. citrumelo, which cause citrus bacterial spot, were, on average, 88% related to each other by DNA reassociation, although these strains exhibited diverse restriction digest patterns. In contrast, strains of X. campestris pv. citri groups A and B, which cause canker A and canker B, respectively, had relatively homogeneous restriction digest patterns. The groups of strains causing these three different citrus diseases were examined by DNA reassociation and were found to be from 55 to 63% related to one another. Several pathovars of X. campestris, previously shown to cause weakly aggressive symptoms on citrus, ranged from 83 to 90% similar to X. campestris pv. citrumelo by DNA reassociation. The type strain of X. campestris pv. campestris ranged from 30 to 40% similar in DNA reassociation experiments to strains of X. campestris pv. citrumelo and X. campestris pv. citri groups A and B. Whereas DNA reassociation quantified the difference between relatively unrelated groups of bacterial strains, restriction endonuclease analysis distinguished between closely related strains.